The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7554/elife.69096
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation among c-subunits of FoF1-ATP synthase in rotation-coupled proton translocation

Abstract: In FoF1-ATP synthase, proton translocation through Fo drives rotation of the c-subunit oligomeric ring relative to the a-subunit. Recent studies suggest that in each step of the rotation, key glutamic acid residues in different c-subunits contribute to proton release to and proton uptake from the a-subunit. However, no studies have demonstrated cooperativity among c-subunits toward FoF1-ATP synthase activity. Here, we addressed this using Bacillus PS3 ATP synthase harboring a c-ring with various combinations o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Organs consuming greater amounts of energy produced by mitochondria more densely packed in their cells are more likely to emit greater amounts of bio photons. Thus, the activity of the brain containing hundreds to thousands of mitochondria in a single neuron 30 , the heart containing more than 5,000 mitochondria in each muscle cell 26 or the liver containing more than 500 mitochondria per single hepatocyte 31 , results in a greater intensity of UPE near the head, chest or stomach, as observed 29,32 . Responsiveness of touch receptor neurons has also been linked with increased mitochondrial density and shorter inter-mitochondrial distances 33 , and this may explain significant contribution of UPE observed on hands 32 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Organs consuming greater amounts of energy produced by mitochondria more densely packed in their cells are more likely to emit greater amounts of bio photons. Thus, the activity of the brain containing hundreds to thousands of mitochondria in a single neuron 30 , the heart containing more than 5,000 mitochondria in each muscle cell 26 or the liver containing more than 500 mitochondria per single hepatocyte 31 , results in a greater intensity of UPE near the head, chest or stomach, as observed 29,32 . Responsiveness of touch receptor neurons has also been linked with increased mitochondrial density and shorter inter-mitochondrial distances 33 , and this may explain significant contribution of UPE observed on hands 32 .…”
Section: Resultsmentioning
confidence: 94%
“…Marked grey F 0 F 1 complex (a) and F 0 unit (b) in ATP synthase/ATPase (a modified drawing based on publication 18 ). (c) The proton flow in the F 0 -ATP synthase (including C-ring) protonic p-n junction system 37 (a scheme based on the structure of ATP synthase/ATPase from 18, 24, 27, 28, 29 ). Preferred (“forward”) proton flow direction with possible light emission is from the “p” to “n” area, like in a protonic diode H + LED 2, 4, 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Although very challenging, direct observations of rotational motions together with proton transfer are warranted. However, a recent study demonstrating the coupling among neighboring c-subunits supports the involvement of a multiply deprotonated state, as described below (Mitome et al, 2022 ).…”
Section: Two or Three C-subunits Are Deprotonated During A Single Rot...mentioning
confidence: 82%
“…Proton transfer-coupled molecular simulations suggested that proton-carrier residues in two or three c-subunits are simultaneously deprotonated while the F O motor rotates. Recently, we examined the coupling of multiple c-subunits in F O through a collaborative study of biochemical assays and molecular simulations of mutant F O motors (Mitome et al, 2022 ). First, Mitome et al ( 2004 ) built a genetically fused single-chain c-ring of Bacillus PS3 ATP synthase.…”
Section: F O -Asp Mutants Exhibited a Characterist...mentioning
confidence: 99%
See 1 more Smart Citation